2011
DOI: 10.1111/j.1751-228x.2011.01122.x
|View full text |Cite
|
Sign up to set email alerts
|

Block Talk: Spatial Language During Block Play

Abstract: Spatial skills are a central component of intellect and show marked individual differences. There is evidence that variations in the spatial language young children hear, which directs their attention to important aspects of the spatial environment, may be one of the mechanisms that contributes to these differences. To investigate how play affects variations in language, parents and children were assigned to 1 of 3 conditions: free play with blocks, guided play, or play with preassembled structures (Study 1). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
166
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(200 citation statements)
references
References 41 publications
7
166
2
6
Order By: Relevance
“…Second, it is possible that parents use more spatial language with boys because boys engage more in spatial activities (e.g., blocks, Legos; Cherney & Voyer, 2010; Kersch, Casey & Young, 2008), and/or find construction activities more attractive (Caldera, Huston & O’Brien, 1985; Campenni, 1999). There is evidence that spatial language occurs more commonly in the context of spatial activities than in the context of non-spatial activities and evidence that boys play more with certain spatial toys than girls, including blocks and Legos (Caldera et al, 1985; Ferrarra, Hirsh-Pasek, Newcombe, Golinkoff & Lam, 2011; Kersh, Casey & Young, 2008; Saracho, 1994) and Legos (Caldera et al, 1985; Campenni, 1999). Third, it is possible that parents hold stereotypes about boys being better at spatial thinking than girls, and as a consequence, may provide boys with more opportunities for spatial play, which could increase boys’ exposure to spatial language.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it is possible that parents use more spatial language with boys because boys engage more in spatial activities (e.g., blocks, Legos; Cherney & Voyer, 2010; Kersch, Casey & Young, 2008), and/or find construction activities more attractive (Caldera, Huston & O’Brien, 1985; Campenni, 1999). There is evidence that spatial language occurs more commonly in the context of spatial activities than in the context of non-spatial activities and evidence that boys play more with certain spatial toys than girls, including blocks and Legos (Caldera et al, 1985; Ferrarra, Hirsh-Pasek, Newcombe, Golinkoff & Lam, 2011; Kersh, Casey & Young, 2008; Saracho, 1994) and Legos (Caldera et al, 1985; Campenni, 1999). Third, it is possible that parents hold stereotypes about boys being better at spatial thinking than girls, and as a consequence, may provide boys with more opportunities for spatial play, which could increase boys’ exposure to spatial language.…”
Section: Discussionmentioning
confidence: 99%
“…Children's play with these simple, three-dimensional geometric building shapes has been linked to the development of convergent and divergent problem-solving skills (Pepler & Ross, 1981), spatial language (Ferrera, Hirsh-Pasek, Newcombe, Golinkoff, & Lam, 2011), logico-mathematical knowledge (Kamii, Miyakawa, & Kato, 2004), and spatial visualization abilities (Caldera et al, 1999) in young children. For example, Caldera et al (1999) conducted in-depth observations of 60 preschool children's structured and unstructured play with blocks and assessed the relationship between particular building behaviors and children's spatial skills.…”
Section: Object Play and The Exploration Of Physical Science Conceptsmentioning
confidence: 99%
“…Thus, as children plan and execute the construction of block structures within play-by stacking and balancing blocks, classifying them by color or shape, and comparing the relative size of different components of their structures-they appear to be engaging in cognitive exercises that foster spatial-mathematical reasoning and can facilitate later academic performance (Ferrera et al, 2011). For example, Wolfgang, Stannard, and Jones (2001, 2003 found that complex block play in preschool (as rated on the Lunzer Five Point Play Scale) had a significant relationship with math achievement measures in middle and high school.…”
Section: Object Play and The Exploration Of Physical Science Conceptsmentioning
confidence: 99%
“…Yet popular shape sorter toys and touchscreen apps typically contain only one, iconic version of each shape category (Dempsey et al, 2013). Furthermore, designing shape materials requiring goal-directed adult involvement (e.g., Ferrara et al, 2011) might result in significantly more exposure to language about geometric forms at younger ages.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, exposure to spatial language (e.g., spatial location words like up or down, deictic terms like here or there, dimensions, shape terms, spatial orientations, etc.) elicits more spatial language production (e.g., Ferrara, Hirsh-Pasek, Newcombe, Golinkoff, & Lam, 2011) and builds later skills such as ability to do spatial transformations and analogies; Pruden, Levine, & Huttenlocher, 2011). Playing with toys that incorporate shapes (e.g., shape sorters), labeling them, and discussing shape properties may be among the earliest spatial experiences parents provide.…”
mentioning
confidence: 99%